Just what I needed - James, Lorelei (James, Lorelei. Need you series., 2016)
"Trinity Carlson might be having the worst day ever. And that was before she started drinking in a dive bar, right across from her ex and his new girlfriend. So when she finally decides enough is enough, she grabs hold of a hot, blond stranger and gives him the kiss of his life"--Page 4 of cover.